Stoner attitude - esteroides antes de los pies: producción de 5 temas inéditos con sonoridad basada en el disco SGT. Peppers lonely hearts club band perteneciente a ´The Beatles´ - Pacheco Braganza, Rafael Alejandro (2019)
The Beatles were an English Rock band from the 60s. They were considered as one of the most commercially successful music groups of all time and also very critically acclaimed in the history of popular music. It was formed by John Lennon (rhythmic guitar - vocals), Paul McCartney (bass - vocals), George Harrison (solo guitar - vocals), and Ringo Starr (drums - vocals). (Davies, 2009) During their musical career in the recording studio, they created much of their best material, including the album Sgt. Pepper’s Lonely Hearts Club Band in 1967, which many consider to be a masterpiece and one of the most influential records of all time. That is why this project proposes to combine and apply, through research and experimentation, the sound techniques used by The Beatles for musical recording and production in Sgt. Pepper’s Lonely Hearts Club Band, with the sound of Stoner Attitude in their five – song album titled Esteroides Antes De Los Pies. (Stoner Attitude is a rock – fusion band from Quito, formed by three members: Rafael Pacheco, Mateo Tenorio, Juan Carlos Soto.) This album is a source of inspiration, reference and influence to many artists nowadays in various aspects such as style, aesthetic, sound, and musical composition itself. That is why this project will have important academic weight, as it complies with every step and study method learned, in order to accomplish the desired result through research and experimentation. The outcome of this project will be a phonogram with five original tracks recreating the sound of the album Sgt. Pepper’s Lonely Hearts Club Band by The Beatles.